Transfer control standards for special training of hockey players undergoing sports training - Medvedev V.G. ,; Davydov A.P. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to establish guidelines for the development and implementation of training protocols for elite hockey players. Methods and structure of the study. The findings from the assessment of 135 hockey players, representing a diverse range of abilities and positions, spanning various age groups (from 9 to 19 years old), were utilized for the purpose of this study. The assessment focused on evaluating the following motor skills of the players: the speed at which they acquire the puck, their agility, and their ability to throw the puck with precision. Results and conclusions. Based on pre-established regression models that enable the extrapolation of the data obtained, and considering the duration of the phases of sports training and the age of individuals for enrollment in these phases in the sport of hockey, control and transfer standards for years and phases of training are proposed: the initial training phase (8 years), the training phase (11 years), the improvement phase of sports skills (15 years), and the phase of advanced sports skills (17 years). The proposed transfer standards are recommended for use in the educational and training process as part of the gradual monitoring of the fitness of hockey players. The article provides a comprehensive explanation of the proposed tests and the method for calculating the necessary indicators.